Bureaucratic Reform Policy Strategy Using The Cipp Model For The Improvement Of Public Services In Kemenko-Polhukam - Sintha Wahjusaputri; Bambang Irawan (Agregat: Jurnal Ekonomi dan Bisnis, 2019)
This study aims to evaluate bureaucratic reform strategies in organizational units within the Coor- dinating Ministry of Politics, Law and Secutiry (Kemenko Polhukam). Bureaucratic Reformation has the main objective of realizing world-class governance characterized by the implementation of effective, efficient, accountable, transparent governance, clean from collusion, corruption and nepo- tism practices or clean government, so that can ultimately improve employees’ performances related to the tasks and functions of the Kemenko Polhukam which are synchronization and coordination of planning, drafting and implementing policies in the fields of politics, law and security. One area of reform that is quite important to improve is public services, especially in the current era of regional autonomy which provides opportunities for regions to innovate, creative, and create the best models for achieving quality improvement for the community. The research methodology used in this study was qualitative research that resulted descriptive data by using the CIPP (Contexts, Input, Process and Product) evaluation model. The results showed that bureaucratic reform in the Coordinating Ministry for Politics and Security was quite good, which increased from the previous year as much as 6.1%. Several bureaucratic strategies were implemented between changing the management, ar- ranging the laws, arranging organization and governance, structuring the HR management system, strengthening supervision, strengthening public accountability teams, improving the quality of public services, monitoring and evaluating the related units.